Stabilization time modeling for hydroprocessing: Identification of the dominant factors. (23rd February 2020) - Cao, Ngoc-Yen-Phuong; Celse, Benoit; Guillaume, Denis; Guibard, Isabelle; Thybaut, Joris W.
Highlights: The dominant factors during hydroprocessing stabilization were assessed. Stabilization time model was constructed using transient data. Good prediction of steady-state performance from transient-state data. Abstract: Hydroprocessing stabilization has been assessed using experimental data acquired at transient conditions. These data were obtained from a hydrotreating pilot plant in a wide range of operating conditions. It has been found that the stabilization evolution follows a first-order response and could be characterized by a stabilization time τ. A linear model was developed to relate τ to its most influential parameters. The model can then be combined with online transient data to predict the steady-state performance. By testing against new data with other feedstocks, the model has been found to provide a good prediction of the stabilization evolution and the ultimate steady-state hydrotreating performance. It is, hence, possible to "online" calculate the steady-state performance without the need to reach this steady state.